Pengaruh Pijat Oksitosin Terhadap Pengeluaran ASI pada Ibu Postpartum Di PMB Nurul Awalia Astarie, A.Md. Keb Kec.Mojoagung Kab.Jombang - Henny Sulistyawati; Yana Eka Mildiana (EMBRIO: Jurnal Kebidanan, 2022)
Oxytocin massage is stimulation that can be given to stimulate milk production. Massage can provide comfort to the mother after the delivery process. This study used a quasi-experimental method with a one-group pre-and post-test design. Measurements were carried out before and after the research intervention. Measurements were made using an observation sheet (breast milk production) and then given an intervention (oxytocin massage) followed by an evaluation on day 3 using an observation sheet (breast milk production). The results of this evaluation were compared with the results of measurements before the intervention was given. The characteristics of the most oxytocin massage respondents, based on age were 20-35 years, 24 respondents (80%), multiparity parity 21 respondents (70%), and normal upper arm circumference 23.5 – 26.5 cm 15 respondents (50%). The breast milk production before the oxytocin massage was carried out with the most breast milk not lagging as many as 25 respondents (83.3%), after the oxytocin massage the milk flow was smooth as many as 28 respondents (93.3%). The results of statistical tests using Mcnemar Test obtained p-value = 0.000 or p < = 0.05. There is an effect of oxytocin massage on milk production in postpartum mothers at PMB Nurul Awalia Astarie, A.Md. Keb. Conclusion Oxytocin massage has an effect on breast milk production in postpartum mothers. Suggestion. It is hoped that as input for knowledge, it can be applied as part of the oxytocin massage intervention for health workers and the public for Smooth Breastfeeding.